PEMBINAAN PEMANFAATAN PEMBELAJARAN AUDIO VISUAL BAGI KREATIVITAS PENDIDIKAN AGAMA ANAK DI GEREJA BETHEL INDONESIA TABITA LOBAM BINTAN - John Karel Moy; Gomgom Purba; Hotnida Panjaitan; Nilawaty Manalu; Komfriska Sitinjak (Unit Penelitian dan Pengabdian Kepada Masyarakat, 2024)
The aim of this research is to determine the development of the use of audio-visual learning for creativity in children's religious education at the Bethel Indonesia Tabita Lobam Church, Bintan. This research is research in the form of field research or field research is a type of research. This research is a qualitative descriptive research. The data in this research comes from primary and secondary data. Data collection methods use observation, interviews and documentation. Interviews were conducted with the community at the PkM location. The research results obtained in the implementation of coaching on the use of audio-visual media consist of several stages. First, the teacher makes preparations by preparing equipment in the form of a projector, sound system, laptop and children's story CDs. Second, the teacher carries out apperception, such as asking questions about the story they are going to learn. Then, the teacher conditions the children to sit neatly and comfortably, after that the teacher shows a video with a duration of 15 minutes. After that, the teacher and children conduct questions and answers regarding the video that has been presented and give the children worksheets to measure the extent to which the children understand the material presented using audio-visual media. With this audio visual learning media, children are able to: increase interest in learning, motivate them in the learning process, and children get a real picture of the concepts being studied and this becomes an advantage in itself. The inhibiting factors in efforts to maximize the use of visual media are human resources, infrastructure and also less than optimal internet signals